2007
DOI: 10.1016/j.labeco.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a large expansion of pre-primary school facilities on preschool attendance and maternal employment

Abstract: Abstract:We provide evidence on the impact of a large construction of pre-primary school facilities in Argentina. We estimate the causal impact of the program on pre-primary school attendance and maternal labor supply. Identification relies on a differences-in-differences strategy where we combine differences across regions in the number of facilities built with differences in exposure across cohorts induced by the timing of the program. We find a sizeable impact of the program on pre-primary school participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
176
3
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(194 citation statements)
references
References 20 publications
11
176
3
4
Order By: Relevance
“…To form credible instrumental variables for individual schooling outcomes that help mitigate the endogeneity of schooling and unobserved ability, institutional features of education system such as compulsory schooling reforms (Harmon and Walker, 1995;Meyer, 2015), tuition costs, geographical proximity (Uusitalo and Conneely, 1998) and schooling construction (Berlinski and Galiani, 2007;Duflo, 2001) have been used. The use of supply-side variables can help resolve identification problems on the demand side of the education market (Card, 2001).…”
Section: Instrumental Variables Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…To form credible instrumental variables for individual schooling outcomes that help mitigate the endogeneity of schooling and unobserved ability, institutional features of education system such as compulsory schooling reforms (Harmon and Walker, 1995;Meyer, 2015), tuition costs, geographical proximity (Uusitalo and Conneely, 1998) and schooling construction (Berlinski and Galiani, 2007;Duflo, 2001) have been used. The use of supply-side variables can help resolve identification problems on the demand side of the education market (Card, 2001).…”
Section: Instrumental Variables Estimationmentioning
confidence: 99%
“…Several studies provide evidence that in developing countries, the supply of schools, in particular, the number of schools or planned schools associates positively with years of education and school enrolment (Berlinski and Galiani, 2007;Duflo, 2001). Lacking comprehensive data on the number of schools, we introduce the number of state primary school teachers per 1000 children as a proxy for school supply.…”
Section: Instrumental Variables Estimationmentioning
confidence: 99%
“…Angeles and colleagues [14] used a fixed effects design and compared mothers with children on daycare waiting lists to those attending the same daycares in the same locality and found differences in maternal employment and hours worked per month, but no impacts on income or measures of mental health. Both Berlinski and colleagues [20] and Calderon [18] used variation in the construction of new preschool facilities to identify the impact on maternal outcomes, and both studies reported positive impacts on maternal employment rates but weak or imprecise effects on maternal work hours. Kilburn [19] and colleagues used a similar design in China and found that the construction of new daycare centers increased wage-related maternal employment by 38 percentage points (95% CI: 13, 63).…”
Section: Resultsmentioning
confidence: 99%
“…Berlinkski and colleagues [16] also reported stronger effects among households with older children. On the other hand, Calderon [18] reported no differences in treatment effect by education or urban/rural status, and Berlinksi and Galiani [20] fail to reject tests of homogeneity by the presence/absence of spouse or child age.…”
Section: Heterogenous Effectsmentioning
confidence: 99%
“…In Argentina, for example, a large-scale program to construct pre-primary school facilities seems to have had a positive impact not only on pre-primary school attendance but also on maternal employment [12]. Despite the complexity of the relationship between maternal employment and child welfare and the ambiguity of some of the evidence, the importance of childcare services for women's employment can hardly be denied.…”
Section: Uganda's Youth Opportunities Programmentioning
confidence: 99%